Szacowanie wolnych przepływów pieniężnych po okresie szczegółowej prognozy w metodach dochodowych wyceny - Kąkol, Wiesław (Estimating Free Cash Flow After Explicite Forecast Period In Income Methods, 2007)
Using in a company valuation income methods are connected with settlement of value of a cash flow before explicite forecast period and the determination of the residual value after this period. The paper presents a review of the current state of knowledge and the author's hypothesis on residual value measurement.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 278-285